Agronomic response of maize to limited levels of water under furrow irrigation in southern Spain - Aguilar, M.=700 1 Borjas, F.; Espiosa, M.
Es, En)
Ilus., 30 ref.
Keywords: RIEGO; ZEA MAYS; PRODUCCION; RENDIMIENTO; ESPAÑA